Pengungkapan CSR Tentang Kinerja Keuangan dan Lingkungan - Intan Novitasari; Darti Djuharni (JIATAX (Journal of Islamic Accounting and Tax), 2019)
This research was conducted to test the effect of CSR on financial performance and add environmental variables as intervening. This type of research is Explonatory research using financial data published on the Indonesia Stock Exchange (IDX). The study was conducted on manufacturing companies in the consumer goods industry sector for three years, namely 2015, 2016, and 2017. From the number listed, they were selected according to the criteria determined to be used as research samples. The number of companies that met the criteria for further analysis was thirteen companies with observations over three years. The results of this study indicate that CSR significantly influences the company's financial performance, and environmental performance as an intervening variable significantly influences the company's financial performance.